Efforts to Improve Learning Motivation and Understanding in Early Children Through Serial Picture And Hand Puppet - Kristiantari, Rini (Universitas Pendidikan Ganesha, 2021)
The learning process that occurs at this time is not optimal. The provision of stimulation to improve children's development is carried out in a straightforward, general way, without enjoyable media stimulation. Students tend to be left to play alone in the schoolyard. It causes students to feel bored in following the lesson. This study aims to develop hand puppets and serial pictures as stimulation media for early childhood. This type of research is development. The research design used research development (R&D) about Borg and Gall with modified stages. The product test subjects studied were kindergarten students individually. The research data was collected using a questionnaire method, then the data collected was analyzed descriptively qualitatively concerning the theory of Miles and Huberman. The results of the media expert test on the five components/indicators rated for serial image media 89.2%, hand puppets 97.2%. The results of the material expert test on five elements/valuable indicators of hand puppets are 100%, and the picture series is 100%. Design expert test results obtained 93% for hand puppets and 80% for serial images. The percentage received shows that both media are feasible to be used to stimulate the growth and development of early childhood language skills. This research implies that teachers can apply the media of hand puppets and serial pictures to increase motivation and learning outcomes of early childhood.